From Hair to Feathers: Clinical Intuition, Ornithology, and Project-Based Learning in Medical Education - Grimalt, Ramon; Murawiec, Sławomir; Tryjanowski, Piotr (Dermatology Review/Przegląd Dermatologiczny, 2025)
This article explores the integration of project-based learning with insights from ornithological observation to foster clinical intuition in medical education, especially in dermatology. By adapting teaching strategies inspired by ornithology and project-based learning, educators can accelerate the development of clinical intuition. We would like to point out the intriguing parallels between birdwatching and clinical reasoning, offering a novel perspective on medical education through the lens of dermatology. Drawing analogies between the pattern recognition used in ornithological observation and the cultivation of clinical intuition, we advocate for project-based learning as an effective educational strategy. Context-rich, collaborative projects promote deep engagement with clinical material, enhance diagnostic skills, and foster critical competencies such as teamwork, motivation, and reflective learning. The integration of this method into dermatology teaching has shown promising results, with increased student engagement and improved clinical reasoning.